EVALUASI IMPLEMENTASI KEBIJAKAN MINIMUM ESSENTIAL FORCE (MEF) PADA POSTUR PEWIRA TNI Jurnal Manajemen & Bisnis Aliansi ANGKATAN UDARA - Sigit Priyono (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The objective of this research was to understand comprehensively of the evaluation of implementation policy ofMinimum Essential Force (MEF) in pertain of human resources focus on officers in the Indonesian Airforce, I was aqualitative recearch with an evaluative method of CIPP model, conducted in Ofiice of Ministry of Defence, IndonesianArmed forces Head quaters, and Indonesian Airforce head quaters, Jakarta.The data were collected through participant observation using interview, observation, document study, andrecording as well as focus group discussion. The data analysis and intrepretation indicates that (1) Indonesiandefence policy to build of minimum essential force by small and more effective with limited of budget; (2) ScopeDefence policy at minimum essential force: (a) Organization (b) Defence Budget (c) Human resources, Three of themare able to protect of the sourvergnity and territorial integrity in the border or in the flash point area; (3) MEF PolicyIn the Indonesian Air Force should be implemented particularly officers as backbond to catch up effectivity, efficiency,equity, and responsiveness of implementation management system in the The Indonesian Air Force organization wasfound to more effective.The findings of this evaluation by CIPP methode scored 3,24 as good result, and give some recommendation topractice continuous improvement to redesign of defence policy by involving of society and in practica to the AirForce organization to reconstruct human resources planning especially for officers.